Modified current collector and preparation method thereof, negative pole piece and battery
By constructing a fluorohydroxyapatite nanomodified layer on the surface of the current collector conductive layer of the negative electrode-free lithium metal battery, the problem of poor cell circulation performance is solved, and higher cycle life and battery performance are achieved.
Patent Information
- Application Number
- CN202411673133.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
The poor circulation performance of negative electrode lithium metal batteries has limited it in large-scale applications, mainly due to the lack of protection of negative electrode active materials and the instability of negative electrode interface, resulting in the generation of 'dead lithium' and lithium dendrites.
The fluorohydroxyapatite nanomodified layer is constructed on the surface of the conductive layer of the current collector, providing a fluorine source to form a stable electrolyte-negative interface, inhibiting the generation of 'dead lithium' and lithium dendrites, and acting as a protective layer to prevent the current collector from being affected by the current collector. The metal layer oxidizes.
By stabilizing the electrolyte-negative interface, reducing the lithium ion desolution barrier, accelerating the interface transmission dynamics, effectively inhibiting the generation of 'dead lithium' and lithium dendrites, thereby significantly improving the cycle life and performance of the battery.
Smart Images

Figure BDA0005146389720000071 
Figure BDA0005146389720000081
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a modified current collector and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] Lithium metal batteries, known for their high energy density, continue to attract attention as a promising next-generation advanced energy storage technology. In particular, negative electrode-free lithium metal batteries eliminate the use of initial negative electrode active materials and can push the full battery energy density to the extreme, exceeding 450Whkg. -1 , is regarded as the ultimate choice for high energy density lithium metal batteries.
[0003] However, for negative electrode-free lithium metal batteries, due to the lack of protection of negative electrode active materials or compensation of excess active lithium, and the "dead lithium" and lithium dendrites caused by the instability of the negative electrode interface during the cycle process, the cycle performance of negative electrode-free lithium metal batteries is poor, which limits the large-scale application of negative electrode-free lithium metal batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a modified current collector and a preparation method thereof, a negative electrode plate and a battery, so as to improve the battery cycle performance and increase the battery cycle life.
[0005] To achieve the above purpose, the technical solution provided by the present invention is:
[0006] The first aspect of the present application provides a modified current collector having a fluorohydroxyapatite nano-modified layer on the surface of the conductive layer of the current collector.
[0007] Due to the introduction of fluorohydroxyapatite nano-modified layer:
[0008] On the one hand, the electrostatic force between phosphate and lithium ions in fluorohydroxyapatite is strong, thus forming a local lithium ion enrichment area, increasing the probability of interaction between anions and lithium ions, forming more lithium ion coordinated anions to stabilize the electrolyte-negative electrode interface. The generated stable interface can reduce the lithium ion desolvation energy barrier, accelerate the interface transmission kinetics, and effectively inhibit the generation of "dead lithium" and lithium dendrites, thereby improving the cycle life of the battery;
[0009] On the other hand, the fluorinated hydroxyapatite nano-modified layer can provide a fluorine source for the formation of the negative electrode SEI film, thereby forming a fluorine-containing SEI film with a lower Fermi level, hindering the transfer of electrons to the electrolyte to reduce the electrolyte, achieving the compatibility and stability of the interface between the current collector and the electrolyte, and improving the performance of the battery; and the formed fluorine-containing SEI film can promote the uniform passage of lithium ions and uniform deposition on the surface of the current collector, inhibiting the generation of dendrites and improving the performance of the battery; in addition, the introduction of this modified layer can act as a protective layer to protect the metal layer of the current collector from air oxidation.
[0010] Furthermore, the molecular formula of the fluorohydroxyapatite is Ca 10 (PO 4 ) 6 (OH) 2-x F x , where 0<x≤2. Within this range, the surface modification layer can provide more fluorine sources for the formation of the negative electrode SEI film, and can form a fluorine-containing SEI film with a lower Fermi level, hinder the transfer of electrons to the electrolyte to reduce the electrolyte, achieve the compatibility and stability of the interface between the current collector and the electrolyte, and further improve the cycle performance of the battery. Exceeding this range may have adverse effects such as promoting electrolyte decomposition, excessive SEI film thickness affecting electronic conduction, and excessive F ions reacting with active substances.
[0011] Furthermore, the current collector conductive layer is selected from a metal foil body of a metal foil current collector, a conductive layer of a composite current collector or a conductive layer of a bipolar current collector.
[0012] Furthermore, the thickness of the fluorohydroxyapatite nano-modified layer is 5-100 nm.
[0013] Preferably, the metal foil current collector is a copper foil current collector, the composite current collector is a composite copper current collector, and the bipolar current collector is a bipolar copper current collector.
[0014] The second aspect of the present application provides a method for preparing a modified current collector, in which a fluorohydroxyapatite nano-modified layer is constructed on the surface of the current collector conductive layer by a magnetron sputtering process.
[0015] Furthermore, the target material used in the magnetron sputtering process is hydroxyapatite, and the gas sources used are argon and carbon tetrafluoride.
[0016] Furthermore, the argon flow rate of the magnetron sputtering process is 0<V≤300mL / min, and the carbon tetrafluoride flow rate is 0<V≤200mL / min.
[0017] Furthermore, the magnetron sputtering process adopts radio frequency magnetron sputtering; the magnetron sputtering power of the radio frequency magnetron sputtering process is 15-40kW, and the deposition time for constructing the fluorohydroxyapatite nano-modified layer is 25-500s.
[0018] The third aspect of the present application provides a negative electrode plate, which includes the modified current collector described in the first aspect of the present application or the modified current collector prepared by the method described in the second aspect of the present application.
[0019] The fourth aspect of the present application provides a battery, which contains the negative electrode plate described in the third aspect of the present application.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention proposes a surface-modified current collector from the perspective of stabilizing the negative electrode interface of a negative electrode-free lithium metal battery to improve the battery cycle performance and increase the battery cycle life; the surface modification treatment is to construct a fluorohydroxyapatite nano-modified layer on the surface of the current collector conductive layer.
[0022] The present invention is based on the surface material and structural design of the current collector, which can alleviate the negative electrode's rejection of free anions, thereby generating sufficient anion derivatives at the electrolyte-negative electrode interface to stabilize the electrolyte-negative electrode interface. The generated stable interface can reduce the lithium ion desolvation energy barrier, accelerate the interface transmission kinetics, and effectively inhibit the generation of "dead lithium" and lithium dendrites, thereby improving the cycle life of the lithium metal battery. DETAILED DESCRIPTION
[0023] The above contents of the present invention are further described in detail below in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.
[0024] The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the reagents, methods and equipment used are all conventional reagents, methods and equipment in the technical field unless otherwise specified.
[0025] For the sake of simplicity, this document only specifically discloses some numerical values and optional ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range; the optional items in the optional range can also be combined arbitrarily.
[0026] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art.
[0027] The present invention proposes a modified current collector and a preparation method thereof, a negative electrode sheet and a battery; the scheme of the present invention can be applied to various types of metal foil current collectors, composite current collectors or bipolar current collectors, and the most commonly used copper foil current collectors, composite copper current collectors and bipolar copper current collectors are specifically described as follows:
[0028] (1) Copper foil current collector:
[0029] Considering the energy density and cost, the preferred thickness range is: 0-10 μm, excluding 0.
[0030] (2) Composite copper current collector:
[0031] The composite copper current collector is composed of three layers, and the structural order is: conductive layer, polymer film, and conductive layer.
[0032] Polymer membranes have the following characteristics:
[0033] ⅰ. The material is one or more of polyethylene terephthalate (PET), polypropylene (PP), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polyethylene (PE), polypropylene, polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), polyphenylene oxide (PPO), polystyrene (PS), polyimide (PI) and the like.
[0034] ⅱ. Considering the application requirements of the composite current collector, namely, light weight to improve battery energy density, while taking into account the difficulty and cost of the preparation process, the preferred thickness of the polymer film is 1.0-10 μm.
[0035] The conductive layer has the following characteristics:
[0036] ⅰ. Located on the surface of the polymer film, it functions as a conductor;
[0037] ⅱ. The material is one or more of copper and its alloys, providing conductivity for the composite current collector;
[0038] ⅲ. The thickness is greater than or equal to 500nm, preferably between 500-2000nm. If the conductive layer is too thin, the conductivity is poor. If the conductive layer is too thick, the prepared composite current collector is too heavy, which is not conducive to improving the energy density of the battery. Considering the conductivity and the improvement of energy density, the more preferred thickness is 800-1200nm.
[0039] iv. It can be prepared by one or more of physical vapor deposition, electroplating, chemical plating, etc.
[0040] (3) Bipolar copper current collector:
[0041] The bipolar copper current collector is composed of two layers, and the structural order is: the first conductive layer and the second conductive layer.
[0042] The first conductive layer has the following characteristics:
[0043] ⅰ. The materials are aluminum, aluminum alloy, nickel, nickel alloy, stainless steel, carbon (such as graphite, carbon nanotubes, carbon fiber, graphene, etc.), conductive polymers (such as polypyrrole, polyacetylene, polyaniline, polythiophene, polyparaphenylene sulfide, polyparaphenylene, etc.).
[0044] ⅱ. The preferred thickness range is 0.5-50 μm. If it is too thin, the conductivity will be poor; if it is too thick, the energy density of the battery will be reduced.
[0045] The second conductive layer has the following characteristics:
[0046] ⅰ. The material is copper or copper alloy;
[0047] ⅱ. The preferred thickness range is 0.5-50 μm; too thin, the conductivity is poor; too thick, the energy density of the battery is reduced;
[0048] The first conductive layer and the second conductive layer can be composited and prepared by one or more methods such as hot pressing, physical vapor deposition, chemical vapor deposition, electrochemical deposition, and chemical deposition.
[0049] The present invention constructs a fluorohydroxyapatite nano-modified layer on the surface of the current collector conductive layer to form a modified current collector. The modified layer is located on the surface of the current collector conductive layer, stabilizes the electrolyte-negative electrode interface, improves the battery cycle performance, and can serve as an anti-oxidation protective layer on the surface of the current collector conductive layer to prevent oxidation of the current collector conductive layer.
[0050] The modified layer material is fluorohydroxyapatite, i.e. Ca 10 (PO 4 ) 6 (OH) 2-x F x , where 0<x≤2, that is, the mass content of fluorine atoms in fluorohydroxyapatite molecules ranges from 0 to 3.77wt.%; the larger the x, the higher the mass content of fluorine atoms. The modified layer can provide more fluorine sources for the formation of the negative electrode SEI film, and can form a fluorine-containing SEI film with a lower Fermi level, hinder the transfer of electrons to the electrolyte to reduce the electrolyte, achieve the compatibility and stability of the interface between the current collector and the electrolyte, and further improve the cycle performance of the battery.
[0051] The modified layer preferably has a thickness of 5-100 nm; more preferably, the modified layer has a thickness of 40-60 nm; if the protective layer is too thin, the effect is not obvious; if the protective layer is too thick, the conductivity of the composite current collector deteriorates and affects the improvement of the battery energy density.
[0052] The modified layer of the present application can be prepared by a reactive magnetron sputtering process, and the following specific process can be used:
[0053] ⅰ. The target material is hydroxyapatite;
[0054] ⅱ. The gas source is argon (Ar) and carbon tetrafluoride (CF 4 ), where Ar generates Ar+ during the sputtering process, bombards the target, induces the target atoms to escape, and then deposits on the copper current collector; CF 4 Provide fluorine atoms during the sputtering process, which react with atoms sputtered from the target to form fluorinated hydroxyapatite;
[0055] Wherein, the Ar flow rate is 0<V≤300mL / min; further preferably, the Ar flow rate is 10≤V≤100mL / min;
[0056] CF 4 The flow rate is 0<V≤200mL / min; further preferably, CF 4 Flow rate: 30≤V≤200mL / min;
[0057] ⅲ. Using radio frequency magnetron sputtering, the frequency is 13.56MHz, the power is preferably 15-40kW, the power is too low, the deposition efficiency is low, the power is too high, it is easy to produce hole defects;
[0058] Among them, the deposition time is 25-500s.
[0059] Working pressure ≤5Pa; cooling temperature is -30℃-0℃.
[0060] The present invention is further described in detail below in conjunction with specific embodiments:
[0061] Example 1
[0062] (1) Preparation of composite copper current collector
[0063] A biaxially stretched PET film with a thickness of 4.5 microns is placed in a vacuum evaporation machine, and copper metal is deposited on both sides of each PET film in turn. The high-purity copper wire (purity greater than 99.99%) in the metal evaporation chamber is melted and evaporated at a high temperature of 1500°C. The evaporated metal atoms pass through the cooling system in the vacuum coating chamber and are deposited on the surface of the PET film to form a copper metal conductive layer with a thickness of 1 micron, thereby obtaining a composite copper current collector with a total thickness of 6.5 microns.
[0064] (2) Preparation of surface modification layer
[0065] The composite copper current collector prepared as above was placed in a magnetron sputtering machine, and its two copper surfaces were subjected to magnetron sputtering treatment. The specific process was as follows: the target material was a hydroxyapatite target material (purity ≥ 99.99%), the power source was a radio frequency power source, the frequency was 13.56 MHz, the power was 25 kW, the working pressure was 1 Pa, the argon flow rate was 60 mL / min, and the CF 4 The flow rate is 50 mL / min, the substrate cooling temperature is -25 °C, and the deposition time is 250 s to obtain fluorohydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 1.5 F 0.5 )The current collector of the modified layer.
[0066] Example 2
[0067] The method is basically the same as Example 1, except that the composite copper current collector is replaced with a commercial 6-micron thick traditional copper foil current collector; and a modified layer is deposited on the copper foil current collector.
[0068] Example 3
[0069] The method is basically the same as Example 1, except that the composite copper current collector is replaced with a 14 μm thick bipolar copper current collector, and the preparation method is as follows:
[0070] A 12-micron aluminum foil (1060 alloy) is placed in a vacuum evaporation machine, and copper metal is deposited on one side. That is, a high-purity copper wire (purity greater than 99.99%) in a metal evaporation chamber is melted and evaporated at a high temperature of 1500°C. The evaporated metal atoms pass through a cooling system in the vacuum coating chamber and are deposited on the surface of the aluminum foil to form a copper layer with a thickness of 1 micron, thereby obtaining a bipolar current collector with a total thickness of 13 microns. A modified layer is deposited on the copper surface of the prepared bipolar current collector, and no modified layer is deposited on the aluminum surface.
[0071] Example 4
[0072] The same as Example 1, except that: during the preparation of the surface modification layer, CF 4 The flow rate was adjusted to 100 mL / min to obtain a fluorohydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 1.0 F 1.0 )The current collector of the modified layer.
[0073] Example 5
[0074] The same as Example 1, except that: during the preparation of the surface modification layer, CF 4 The flow rate was adjusted to 200 mL / min to obtain a fluorohydroxyapatite (Ca 10 (PO 4 ) 6 F 2 )The current collector of the modified layer.
[0075] Example 6
[0076] It is basically the same as Example 1, except that the deposition time in the process of preparing the surface modification layer is 25 s.
[0077] Example 7
[0078] It is basically the same as Example 1, except that the deposition time in the process of preparing the surface modification layer is 500s.
[0079] Example 8
[0080] It is basically the same as Example 1, except that the magnetron sputtering power during the preparation of the surface modification layer is 15 kW.
[0081] Example 9
[0082] It is basically the same as Example 1, except that the magnetron sputtering power during the preparation of the surface modification layer is 40 kW.
[0083] Comparative Example 1
[0084] The method is basically the same as Example 1, except that no fluorohydroxyapatite nano-modified layer is prepared.
[0085] Comparative Example 2
[0086] The same as Example 1, except that CF was not introduced during the preparation of the modified layer. 4 .
[0087] Comparative Example 3
[0088] It is basically the same as Example 1, except that the deposition time during the preparation of the surface modification layer is 15 s.
[0089] Comparative Example 4
[0090] It is basically the same as Example 1, except that the deposition time during the preparation of the surface modification layer is 525s.
[0091] Comparative Example 5
[0092] It is basically the same as Example 1, except that the magnetron sputtering power during the preparation of the surface modification layer is 42 kW.
[0093] Test evaluation:
[0094] Here, the cycle performance of the surface-modified current collector prepared based on the present invention and the negative electrode-free lithium metal battery assembled therein is tested, and the specific test method is as follows:
[0095] (1) Surface modified current collector:
[0096] ①Thickness of surface modification layer:
[0097] The prepared current collector is prepared according to the sample preparation requirements of the focused ion beam field emission microscope (FIB-SEM), and then the sample is placed in the FIB-SEM. The sample is cut by the ion beam to prepare a cross-sectional sample. After the cross-sectional sample is prepared, the cross-section is observed by the field emission microscope lens, magnified 50,000 times, and after adjusting the clarity, the thickness of the modified layer in the cross-sectional morphology photograph is measured using the measurement software that comes with the electron microscope, thereby obtaining the thickness data of the modified layer.
[0098] ② Antioxidant properties:
[0099] The change in square resistance before and after baking was used for indirect characterization. Specifically, the prepared flat composite current collector sample and the composite current collector sample baked at 150°C for 30 min were placed on a sample table, and the square resistance of the samples was tested using a four-probe square resistance meter. The square resistance change rate was calculated according to the formula (square resistance after baking - resistance before baking) / resistance before baking × 100%. The smaller the change rate, the better the antioxidant performance.
[0100] ③Number of hole defects:
[0101] The prepared current collector sample is placed in a surface quality detection system (micro-vision charge coupled device CCD), its surface is scanned, and then the optical signal is converted into an electrical signal and transmitted to a computer to count the number of hole defects per unit area of the composite current collector.
[0102] (2) Assembled negative electrode-free lithium metal battery:
[0103] ①Assembly of negative electrode-free lithium metal battery:
[0104] For composite current collectors and traditional metal foil current collectors, the assembly process is as follows:
[0105] For the negative electrode, the composite copper current collector and the traditional copper foil current collector in the above embodiment and comparative example are used as the negative electrode;
[0106] For the positive electrode, the positive current collector is made of aluminum foil (12 μm), and the positive electrode materials include lithium iron phosphate, conductive carbon (Super P), carbon nanotubes, and polyvinylidene fluoride, with a mass ratio of 96:1.6:0.7:1.7; for the electrolyte, the electrolyte is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate (LiNO3), with the contents of 1 mol·L -1 , 2wt.%, the electrolyte is 1,2-dimethoxymethane (DME) and 1,3-dioxolane (DOL), and the volume ratio of the two is 1:1; for the separator, a polypropylene separator (thickness of 20μm) is used; using the above materials, a negative electrode-free lithium metal battery is assembled according to the relevant process, and the battery capacity is 1Ah.
[0107] For the bipolar current collector, the assembly process is as follows:
[0108] For the negative electrode, the copper surface of the bipolar current collector in the above embodiment is used as the negative electrode; for the positive electrode, the aluminum surface of the bipolar current collector is used as the positive current collector, and the positive electrode material includes lithium iron phosphate, conductive carbon (Super P), carbon nanotubes, and polyvinylidene fluoride, and the mass ratio is: 96:1.6:0.7:1.7; for the electrolyte, the electrolyte is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate (LiNO3), and the content is 1 mol·L -1, 2wt.%, the electrolyte is 1,2-dimethoxymethane (DME) and 1,3-dioxolane (DOL), and the volume ratio of the two is 1:1. For the diaphragm, a polypropylene diaphragm (thickness of 20μm) is used; using the above materials, a negative electrode-free lithium metal bipolar battery is assembled according to the relevant process, and the battery capacity is 1Ah.
[0109] ②Cyclic performance test:
[0110] The battery prepared as above was placed in a cycle performance test device, and a charge and discharge cycle experiment was carried out at a rate of 0.2C and a cycle charge and discharge voltage range of 3.0V-3.8V. The battery capacity retention rate after 100 cycles of charge and discharge was recorded. The results are shown in Table 1.
[0111] Table 1 Cyclic performance test results of various embodiments and comparative examples
[0112]
[0113]
[0114] The test results are analyzed as follows:
[0115] It can be seen from Examples 1-9 and Comparative Example 1 that: compared with the traditional copper current collector, the surface-modified copper current collector provided by the present invention has a square resistance change rate of 0 before and after baking, indicating that it has good oxidation resistance; and when used in a negative-electrode-free lithium metal battery, the cycle performance of the battery can be significantly improved. This is due to the introduction of the fluorohydroxyapatite nano-modified layer: on the one hand, the electrostatic force between the phosphate radical and the lithium ion in the fluorohydroxyapatite is strong, thereby forming a local lithium ion-enriched area, increasing the probability of interaction between the anion and the lithium ion, and forming more lithium ion-coordinated anions to stabilize the electrolyte-negative electrode interface, generating The stable interface formed can reduce the energy barrier for lithium ion desolvation, accelerate the interface transport kinetics, and effectively inhibit the generation of "dead lithium" and lithium dendrites, thereby improving the cycle life of the battery; on the other hand, the fluorinated hydroxyapatite nano-modified layer can provide a fluorine source for the formation of the negative electrode SEI film, thereby forming a fluorine-containing SEI film with a lower Fermi level, hindering the transfer of electrons to the electrolyte to reduce the electrolyte, achieving the compatible stability of the interface between the current collector and the electrolyte, and improving the performance of the battery; and the formed fluorine-containing SEI film can promote the uniform passage of lithium ions and uniform deposition on the surface of the current collector, inhibiting the generation of dendrites and improving the performance of the battery.
[0116] It can be seen from Examples 1-3 that the modified layer proposed in the present invention has good applicability on composite copper current collectors, traditional copper foil current collectors and bipolar current collectors.
[0117] It can be seen from Examples 1, 4, 5 and Comparative Example 2 that: by increasing the fluorine content in fluorohydroxyapatite, the square resistance change of the prepared copper current collector before and after baking first drops to 0 and then remains unchanged, that is, the antioxidant performance first improves and then remains unchanged. This is because the fluorohydroxyapatite modified layer has a good barrier effect, which can prevent air from penetrating the modified layer to contact the copper layer, thereby avoiding corrosion of the copper layer; by increasing the fluorine content in fluorohydroxyapatite, the charge and discharge cycle performance of the battery assembled with the prepared copper current collector is improved. This is because the content of fluorine atoms in the fluorohydroxyapatite nano-modified layer is increased, and the surface modified layer can provide more fluorine sources for the formation of the negative electrode SEI film, and can better form a fluorine-rich SEI film with a lower Fermi level, hinder the transfer of electrons to the electrolyte to reduce the electrolyte, improve the compatibility and stability of the interface between the current collector and the electrolyte, and further promote the cycle performance of the battery.
[0118] It can be seen from Examples 1, 6, 7 and Comparative Examples 3 and 4 that: by increasing the magnetron sputtering deposition time, the thickness of the prepared modified layer increases, and the square resistance change of the prepared copper current collector before and after baking first drops to 0 and then remains unchanged, that is, the antioxidant performance first increases and then remains unchanged; this is because the increase in the thickness of the fluorohydroxyapatite modified layer can effectively block air from penetrating the modified layer to contact the copper layer, preventing the copper layer from corroding. The square resistance of the prepared copper current collector first remains unchanged and then increases, that is, when the modified layer is too thick, the resistance of the copper current collector will increase; the charge and discharge cycle performance of the battery assembled with the prepared copper current collector first increases and then decreases, this is because increasing the thickness of the modified layer can better stabilize the interface between the electrolyte and the negative electrode, and the generated stable interface can reduce the lithium ion desolvation energy barrier, accelerate the interface transmission kinetics, and effectively inhibit the generation of "dead lithium" and lithium dendrites, thereby improving the cycle life of the negative electrode-free lithium metal battery. However, when the modified layer is too thick, the resistance of the copper current collector will increase, thereby increasing the internal resistance of the battery, and ultimately causing the battery cycle performance to deteriorate.
[0119] It can be seen from Examples 1, 8, 9 and Comparative Example 5 that: by increasing the magnetron sputtering power, the thickness of the prepared modified layer increases, and the hole defects of the prepared surface-modified copper current collector first remain unchanged and then increase, resulting in the cycle performance of the assembled battery first increasing and then decreasing.
[0120] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.
Claims
1. A modified current collector, characterized in that: A fluorohydroxyapatite nano-modified layer is provided on the surface of the conductive layer of the current collector.
2. The modified current collector according to claim 1, characterized in that: The molecular formula of the fluorohydroxyapatite is Ca 10 (PO4)6(OH) 2-x F x , where 0<x≤2.
3. The modified current collector according to claim 1, characterized in that: The current collector conductive layer is selected from the metal foil body of the metal foil current collector, the conductive layer of the composite current collector or the conductive layer of the bipolar current collector.
4. The modified current collector according to claim 1, characterized in that: The thickness of the fluorohydroxyapatite nano-modified layer is 5-100 nm.
5. The modified current collector according to claim 3, characterized in that: The metal foil current collector is a copper foil current collector, the composite current collector is a composite copper current collector, and the bipolar current collector is a bipolar copper current collector.
6. A method for preparing a modified current collector, characterized in that: A fluorohydroxyapatite nano-modified layer is constructed on the surface of the current collector conductive layer by a magnetron sputtering process.
7. The method for preparing the modified current collector according to claim 6, characterized in that: The target material used in the magnetron sputtering process is hydroxyapatite, and the gas sources used are argon and carbon tetrafluoride; the flow rate of the argon is 0<V≤300mL / min, and the flow rate of the carbon tetrafluoride is 0<V≤200mL / min.
8. The method for preparing the modified current collector according to claim 5, characterized in that: The magnetron sputtering process adopts radio frequency magnetron sputtering; the magnetron sputtering power of the radio frequency magnetron sputtering process is 15-40kW, and the deposition time for constructing the fluorohydroxyapatite nano-modified layer is 25-500s.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the modified current collector according to any one of claims 1 to 5 or the modified current collector prepared by the method according to any one of claims 6 to 8.
10. A battery, characterized in that: The battery comprises the negative electrode sheet according to claim 9.